Community Participation in Local Political Processes: A Systematic Literature Review - Hartaman, Nursaleh; Putra, Muhammad Amril Pratama; Alim, Irwan (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2023)
The purpose of this study was to use a systematic literature review technique to describe and thoroughly investigate the understanding of community participation in the local political context. this framework, the role of community participation is considered a crucial element that has a significant impact in the process of policy formation and determining the direction of decision making at the local level. Involving the community in the local political process is not only an indicator of the health of democracy, but also the main basis for creating policies that are more representative and responsive to the needs and aspirations of local communities. By detailing these dimensions of community participation through a systematic literature review, this research aims to provide a solid conceptual foundation for understanding the complex dynamics involved in interactions between communities and local politics. The research results show several dominant themes in this study, such as Political participation and Community Participation. Furthermore, the themes that are most closely linked in this study are community development and developing countries. The most interesting finding in the in-depth study of local politics is the existence of several keywords that are closely related, such as broken window and disability.